A multi-source fluid queue based stochastic model of the probabilistic offloading strategy in a MEC system with multiple mobile devices and a single MEC server - Zheng, Huan; Jin, Shunfu (Zielona Góra: Uniwersytet Zielonogórski)
Mobile edge computing (MEC) is one of the key technologies to achieve high bandwidth, low latency and reliable service in fifth generation (5G) networks. In order to better evaluate the performance of the probabilistic offloading strategy in a MEC system, we give a modeling method to capture the stochastic behavior of tasks based on a multi-source fluid queue. Considering multiple mobile devices (MDs) in a MEC system, we build a multi-source fluid queue to model the tasks offloaded to the MEC server.
Keywords: mobile edge computing; probabilistic offloading strategy; multi-source fluid queue; birth-and-death process; cumulative distribution function